2016
DOI: 10.1002/slct.201600283
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Deactivated Hollow Titanium Silicalite Zeolite from Commercial Ammoximation Process by Encapsulating Amorphous TiO2-SiO2Nanoparticles inside Zeolite Crystal

Abstract: An efficient regeneration method to encapsulate the poisonous amorphous TiO 2 -SiO 2 nanoparticles within zeolite crystal via post-synthesis has been developed. It is demonstrated that the encapsulation of Ti-rich nanoparticles can reduce the accessibility of H 2 O 2 molecules to acid sites of Ti-rich nanoparticles, thus lowering the inefficient decomposition of H 2 O 2 oxidant during catalytic reactions. Furthermore, the regenerated HTS zeolite is of smaller particle size than conventional TS-1 zeolite due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In addition, in our previous works, the irreversible deactivation of HTS zeolite has been investigated by using multiple characterization methods and catalytic evaluations [64][65][66]. It is confirmed that the dissolution of framework Si atoms and the removal of framework Ti atoms cause the formation of acidic amorphous TiO 2 -SiO 2 nanoparticles, leading to the inefficient decomposition of H 2 O 2 molecules during catalytic oxidation processes.…”
Section: Ammoximation Of Ketones With H 2 O 2 and Nhmentioning
confidence: 81%
“…In addition, in our previous works, the irreversible deactivation of HTS zeolite has been investigated by using multiple characterization methods and catalytic evaluations [64][65][66]. It is confirmed that the dissolution of framework Si atoms and the removal of framework Ti atoms cause the formation of acidic amorphous TiO 2 -SiO 2 nanoparticles, leading to the inefficient decomposition of H 2 O 2 molecules during catalytic oxidation processes.…”
Section: Ammoximation Of Ketones With H 2 O 2 and Nhmentioning
confidence: 81%
“…It is widely accepted that nonframework Ti species in titanosilicates include amorphous SiO 2 –TiO 2 mixed binary oxides and crystalline anatase, which are harmful to the reaction system by accelerating the decomposition of H 2 O 2 via the free radical mechanism. Ammoximation occurs in an alkaline environment, and the gradual dissolution of the framework Si atoms results in the migration of framework Ti atoms to extra-framework positions, which is the main reason for the generation of amorphous SiO 2 –TiO 2 mixed binary oxides and the irreversible deactivation of catalyst. We investigated the effects of TS-1 containing only framework isolated tetrahedrally coordinated Ti species, SiO 2‑ TiO 2 mixed binary oxides, and crystalline anatase on the oxidation decomposition of NH 2 OH, respectively.…”
Section: Resultsmentioning
confidence: 99%